Constructive Analysis Of The Existence Of Constitutional Court Decisions In The National Legal System - Gilang Indra Friyana Rahmat; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
Protection of citizens' human rights is one aspect that is highly emphasized in the construction of a democratic rule of law and is one of the reasons for the institutionalization of the Constitutional Court. As one of the aspects that is an essential form of the rule of law, the protection of human rights is a very interesting study to analyze, especially in aspects of the implementation of the 2024 General Election. This research uses normative legal research methods with a case approach and qualitative analysis methods. The results of this research are about the importance of protecting citizens' human rights, especially in the context of elections as a means of achieving national democracy. Meanwhile, the advice given in this research is that the law must provide wide space for the institutionalization of Constitutional Court decisions and as a form of confirmation that the Constitutional Court's decisions are binding on the entire community and become a form of public policy that begins with reviewing laws against laws. Constitution of the Republic of Indonesia.